2017
DOI: 10.3945/jn.117.253955
|View full text |Cite
|
Sign up to set email alerts
|

Fructo-oligosaccharide-Induced Transient Increases in Cecal Immunoglobulin A Concentrations in Rats Are Associated with Mucosal Inflammation in Response to Increased Gut Permeability

Abstract: The mechanism underlying transient increases in immunoglobulin (Ig) A concentrations in the cecal contents of rats fed fructo-oligosaccharide (FOS) is unclear. This study was designed to test whether increased IgA concentrations represent one aspect of the inflammatory response to increased permeability induced by FOS in the cecum. Seven-week-old male Wistar rats were fed a fiber-free semipurified diet (FFP) with or without supplemental FOS (60 g/kg diet) for 9 or 58 d [experiment (expt.) 1], 7 d (expt. 2), or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…Cecal fermentation in rats fed 6% FOS diet for 1 wk was characterized by a very low cecal pH (well below 6.0) accompanying the accumulation of lactate and succinate, which are stronger acids than short-chain fatty acids (SCFA) but are absorbed more slowly (12). In such a cecal environment, we found that the mucus layer on the epithelial surface in the cecum was completely destroyed, and this might be associated with the increased gut permeability (11). But in rats fed the same diet for 8 wk, at which time the cecal pH became almost neutral and SCFA were major fermentation products, the gut permeability returned to its nor-mal level (11).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Cecal fermentation in rats fed 6% FOS diet for 1 wk was characterized by a very low cecal pH (well below 6.0) accompanying the accumulation of lactate and succinate, which are stronger acids than short-chain fatty acids (SCFA) but are absorbed more slowly (12). In such a cecal environment, we found that the mucus layer on the epithelial surface in the cecum was completely destroyed, and this might be associated with the increased gut permeability (11). But in rats fed the same diet for 8 wk, at which time the cecal pH became almost neutral and SCFA were major fermentation products, the gut permeability returned to its nor-mal level (11).…”
mentioning
confidence: 82%
“…Many factors could be involved in the above-mentioned different findings of FOS on gut permeability. Our recent study, however, showed that FOS-induced increase in the gut permeability in rats fed a SP was a transient phenomenon before adaptation of the gut bacteria to FOS (11). Cecal fermentation in rats fed 6% FOS diet for 1 wk was characterized by a very low cecal pH (well below 6.0) accompanying the accumulation of lactate and succinate, which are stronger acids than short-chain fatty acids (SCFA) but are absorbed more slowly (12).…”
mentioning
confidence: 97%
“…12) Fecal IgA was extracted using phosphate-buffered saline containing a protein inhibitor cocktail (cOmplete tablets; Roche, Manheim, Germany) as previously described. 13) Fecal IgA content was measured using a Mouse IgA kit (Bethyl Laboratories, Montgomery, TX, U.S.A.).…”
Section: Ethical Approval Of the Study Protocol Experimentsmentioning
confidence: 99%
“…SCFAs in the cecal contents were analyzed as per our previous study. 13) The SCFA content in each sample was calculated using an internal standard method with 2-ethylbutyrate as the standard.…”
Section: Measurement Of Scfas In Cecal Contentsmentioning
confidence: 99%
“…IgA defends epithelial cells from infection and injury from pathogens and microbes in the intestines and improves intestinal conditions . Some polysaccharides and oligosaccharides can induce intestinal release of IgA, but transient induction of IgA release by polysaccharides and oligosaccharides might be caused by mucosal inflammation . We collected feces at 10 weeks and showed increased IgA levels in the HFD‐RS group, suggesting that induction of fecal IgA in the HFD‐RS group was not transient and not due to mucosal inflammation.…”
Section: Resultsmentioning
confidence: 91%